Apprenticeship and vocational education : an institutional analysis of workplace learning in the German Vocational System - Gerholz, Karl-Heinz [Verfasser]; Brahm, Taiga [Verfasser] (My University, 2014)
"Apprenticeship in the German vocational system is organized as a dual system with both workplace and school-base trainings. This dual system has a long successful history in Germany, which is visible, for instance in a stable transition from the dual system to employment and low youth unemployment rate. A main factor for this success is the regulative structure of the German dual system in the society. Accordingly, this chapter analyses this structure from an institutional point of view. The relevant institutions regulate the actions of people in the dual system. These institutions act on different levels, enabling workplace learning in the dual system. Examples for the institutions are the concepts of vocations and occupational competence, the principles of consensus and corporatism an well as action orientation. The institutions have different roles to play, and not all institutions have the same power. Nevertheless, as one result can be mentioned, the quality of workplace learning is assured since people involved appreciate apprenticeship as an institution." (Authors' abstract ; BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; S 3.2 Unternehmen und Behörden; Berufsbildungssystem; Duales System; Beruflichkeit; Berufsschule; Lernort Betrieb; Lernen am Arbeitsplatz; Bundesrepublik Deutschland